The Protection for Citizen During Outbreaks: The Emergency Status During Covid-19 in the Perspective of Indonesian Constitutional Law - Ahmad Ilham Fachriza; Mao Lai Pan (Universitas Negeri Semarang, 2023)
The aim of this research is to contribute novel insights into the emergency measures mandated by the Indonesian government. Employing normative research without a conceptual orientation, the study delves into the transformative developments in Indonesia that have influenced the application of law, particularly in the realm of state administration law during emergencies. This involves two key components: the legal framework, encompassing constitutional and legislative provisions for emergencies, and the operational framework, which includes organizational structures and strategic plans for managing emergencies. In response to the initial developments, the government is compelled to implement a lockdown, as dictated by the principles of emergency state administration law. The execution of a lockdown necessitates resolute action and collaborative efforts from all stakeholders. Moreover, it is imperative to impose limitations on lockdown measures through legal norms, such as a presidential decree, to prevent arbitrary exercise of power by the government. A comprehensive understanding of these dynamics is crucial for the effective functioning of the country.